The Bond Strength and Damping Properties of Mortar Joint Using Rubber Tire Crumbs - Faizah, Restu; Priyosulistyo, Henricus; Aminullah, Akhmad (2022)
Recently, the utilization of rubber from used car tires known as rubber tire crumbs (RTC) was an interesting discussion in the world. Many researchers have studied the utilization of RTC in Civil Engineering field, which is the RTC as a substitute material for the sand part in concrete or mortar mixtures. The mortar using RTC (RTC-mortar) was also proposed to apply as a mortar joint on masonry walls. The strength of the bond between the mortar and the brick is needed to withstand the in-plane loads, such as shear strength, ductility, and damping capacity. This study investigated the bond strength, shear modulus, stiffness, and damping properties of the RTC-mortar joint due to horizontal cyclic load due to earthquake in-plane load. Mortar specimens consisted of normal mortar (0 RTC) and RTC-mortar with 20, 40 and 60 RTC contents. This study results in the prediction of the optimum content of rubber tire crumbs (RTC) in a mortar mixture to be applied as a mortar joint on a masonry wall, which is 20 of sand volume. Mortar joint using 20 RTC content have the bond strength of 0.361 MPa and a damping ratio of 14.9. Based on previous research, the use of mortar containing 20 RTC as a mortar joint of masonry wall also meets the strength requirements, where the compressive strength of mortar joint must exceed the compressive strength of the brick unit. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.